Quantitative Determination of Cerberin in Seed Extract of Cerbera odollam and Rat Serum by High Performance Thin Layer Chromatography - S. S. Prasanth, Rajasekaran Aiyalu (Journal of Applied Pharmaceutical Science, 2015)
Cerberin (2-o-Acetyl neriifolin) is the principal cardiac glycoside present in the seeds of Cerbera odollam (Fig 1) belonging to Apocynacea family. The seeds of Cerbera odollam are used as a poison for suicidal as well as homicidal purpose by people around the world. Its detection in the body fluids is somewhat difficult. The present study aims to develop a HPTLC method to identify and quantify Cerberin present in the seeds of Cerbera odollam and Cerberin present in Rat Serum. Chloroform and methanol in the ratio of 9.6:0.4 v/v was employed as mobile phase for Cerberin. Linear ascending development was carried out in a 10 x 10 cm twin trough glass chamber (CAMAG) saturated with the mobile phase. Detection and quantitation was performed by densitometric scanning at 254 nm, using deuterium lamp. The proposed HPTLC method provided a good resolution of Cerberin in ethylacetate/ethanol extract of seeds of Cerbera odollam and Cerberin present in rat serum, confirmed by overlaying UV absorption spectra with standard cerberin marker. The method found to be rapid, simple and precise and may be employed for the detection and quantification of cerberin in human serum, aspirates and other body fluids.
Keywords: HPTLC, Cerberin, Rat serum.